Application of hydro-mathematical models for flood forecast and inundation warning of Tra Khuc-Ve River basins - Anh, Luong Tuan (VNU Journal of Science: Earth and Environmental Sciences, 2011)
Abstract. The papers present the results of study on application of rainfall-runoff, channel routing models for improvement and extending forecast lead time and Diffusion Hydrodynamic Model (DHM) for inundation warning of Tra Khuc and Ve river basins. Keywords : Time of concentration T c , update of forecast errors, flood forecast, inundation warning.